COVID-19 crisis and resilience of tourism SME's: a focus on policy responses - Estiri, Mehrdad; Heidary Dahooie, Jalil; Skare, Marinko (Economic research - Ekonomska istraživanja, 2022)
Government policy responses play a significant role in increasing the resilience of small and medium-sized tourism enterprises during crisis periods. Proper selection and implementation of these policies is one of the major challenges facing tourism policy makers. The aim of this article is to propose a systematic framework for selecting government supportive policies that contribute effectively to resilience improvements of tourism SMEs during the COVID-19 disaster. After reading the international reports of the COVID-19 disaster carefully and using similar research findings in past disasters as the preliminary stage of framework development, a comprehensive list of country-based recovery policy responses as well as the critical success factors (CSFs) of tourism SMEs in the crisis recovery phase was extracted and then finalized in an expert-oriented process. In the next stage, the Z-SWARA was applied to weigh the CSFs. Then, four Z-MADM methods were implemented to rank the alternatives, and finally, the results were compounded with BORDA technique. The results of implementing the proposed framework in Iran's tourism industry show that Disaster management planning capability, as well as Marketing management are the most important CSFs. Also, financial support including direct lending and grants and subsidies to SMEs have been identified as the most effective governments' supportive policies to recover tourism SMEs in the post-disaster phase. Generally, these results have valuable implications for different stakeholders such as policymakers, practitioners and researchers in the tourism industry.